The Traditional Sekaten Ceremony at the Kasunanan Palace in Surakarta: A Reflection of Islamic Culture - Sawitri (CV. Kalimasada Group, 2025)
Purpose -This study examines the Sekaten ceremony at the Kasunanan Palace in Surakarta and Yogyakarta as a reflection of Javanese-Islamic civilization. It aims to analyze the religious significance of this tradition in commemorating the birthday of Prophet Muhammad SAW and the Islamic New Year. Design/Methodology/Approach - A qualitative approach was used, combining traditional methods like observation, interviews, and documentation with modern digital ethnography, including the analysis of videos and TikTok content. Findings - The research shows that Sekaten bridges 16th-century Javanese roots with deep Islamic values. While aesthetic elements like Gamelan Guntur Madu and Guntur Sari remain central, the use of agricultural products, such as tumpeng and jodhang to symbolizes communal gratitude for a prosperous life. These rituals function as a reflection of faith, allowing the Javanese community to unite in a religious and cultural celebration. Originality/Value - This article highlights the resilience of ancient traditions in the digital age. By integrating modern social media platforms like TikTok into the study of a centuries-old ritual, it provides a unique perspective on how Islamic civilization maintains its meaning amidst globalization.